Explore the role of Decision Support Systems (DSS) in enhancing decision-making processes across different business functions finance, marketing, and supply chain - ALATTAR , ALHASAN (The Gulf Economist, 2025)
The paper examines decision support systems (DSS) from both theoretical and practical perspectives, showing how modern DSS especially those enhanced by AI and ML significantly improve decision-making and operational performance. Case studies from major companies and three key sectors (retail, healthcare, manufacturing) demonstrate gains in efficiency, accuracy, and cost reduction. The study concludes that DSS are powerful tools that enhance strategic decisions and organizational competitiveness, despite challenges like data quality and user adoption